Analisis Komparatif Pengaruh Transformational Leadership terhadap Kinerja Sekolah yang Dimediasi Stakeholder Engagement pada SMP Negeri dan SMP Swasta di Jawa Timur - Dewie Tri Wijayati (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
The purpose of this study is to analyze the application of transformational leadership patterns to support the realization of changes in the school system. The type of research used is explanatory with a quantitative approach. The population of this research is Public and Private Junior High Schools in Surabaya. The sample taken in this study was 40 schools. The data obtained were processed using SEM (Structural Equation Modeling) with the Smart PLS version 3.0 application program. The results provide empirical evidence to confirm that: transformational leadership has a positive effect on school performance; transformational leadership has a positive effect on stakeholder engagement; stakeholder engagement has a positive effect on school performance; stakeholder engagement mediates a positive transformational leadership relationship with school performance.